Efficacy of an in-home test kit in reducing dust mite allergen levels: results of a randomized controlled pilot study. (7th February 2016) - Winn, Amber K.; Salo, Päivi M.; Klein, Cynthia; Sever, Michelle L.; Harris, Shawn F.; Johndrow, David; Crockett, Patrick W.; Cohn, Richard D.; Zeldin, Darryl C.
Abstract: Background : Dust mite allergens can induce allergic sensitization and exacerbate asthma symptoms. Although dust mite reduction and control strategies exist, few asthmatics employ them. Objectives : We examined whether an in-home test kit, which quantifies dust mite allergen levels, resulted in behavioral changes in implementation and maintenance of mite reduction strategies and helped reduce allergen levels in homes of dust mite-sensitive children. Methods : We enrolled 60 households of children aged 5–15 with parent-reported dust mite allergy into a randomized controlled trial. Intervention homes ( N = 30) received educational material about reducing dust mites and test kits at 1, 2, 5 and 8 months. Control homes ( N = 30) received only educational material. At baseline, 6 and 12 months, study staff visited all homes, collected dust samples from three locations and obtained information about parents' mite reduction behaviors by questionnaire. Allergen concentrations ( Der f 2/Der p2 ) in dust were assessed by immunoassays. After adjusting for visit and location, allergen concentrations in intervention and control homes were compared using mixed effects model analysis. Results : In the intervention homes, allergen concentrations in the child's bedroom and living room floors were significantly reduced over time compared to control homes. Although not all location-specific differences in allergen concentrations were statistically significant, combining data across locations, there was a differential reduction in allergen concentrations in the intervention group versus the control group ( p = 0.02). Conclusion : The use of in-home test kits along with education may beneficially influence behaviors and attitudes toward dust mite reduction strategies and help reduce residential dust mite allergen levels.